512-Channel and 13-Region Simultaneous Recordings Coupled with Optogenetic Manipulation in Freely Behaving Mice - Xie, Kun; Fox, Grace E.; Liu, Jun; Tsien, Joe Z. (Frontiers in Systems Neuroscience, 2016)
The development of technologies capable of recording both single-unit activity and local field potentials over a wide range of brain circuits in freely behaving animals is key to constructing brain activity maps. Although mice are the most popular mammalian genetic model, in vivo neural recording has been traditionally limited to smaller channel count and fewer brain structures because of the mouse’s small size and thin skull. Here, we describe a 512-channel tetrode system that allows us to record simultaneously over a dozen cortical and subcortical structures in behaving mice. This new technique offers two major advantages - namely, the do-it-yourself, ultra-low cost and the greater flexibility for targeting any combination of many brain areas. We show the successful recordings of both single units and local field potentials from 13 distinct neural circuits of the mouse brain, including subregions of the anterior cingulate cortices, retrosplenial cortices, somatosensory cortices, secondary auditory cortex, hippocampal CA1, dentate gyrus, subiculum, lateral entorhinal cortex, perirhinal cortex and prelimbic cortex. This 512-channel system can also be combined with Cre-lox neurogenetics and optogenetic manipulation to further examine interactions between genes, cell types, and circuit dynamics across a wide range of brain structures. Finally, we demonstrate that complex stimuli - such as earthquake and fear-inducing foot-shock - trigger firing changes in all of the recorded 13 brain regions, supporting the notion that neural code is highly distributed. In addition, we show that localized optogenetic manipulation in any given brain region disrupted network oscillations and caused changes in single-unit firing patterns in a brain-wide manner, thereby raising the cautionary note of the interpretation of optogenetically manipulated behaviors.